Chapter: ''Anachronistic As Colonial Remnants May Be...' Locating the Rights of the Chagos Islanders As a Case Study of the Operation of Human Rights Law in Colonial Territories' from book: Fifty Years of the British Indian Ocean Territory: Legal Perspectives - Ralph Wilde (The World of Small States, 2018)
In the colonial era, it was commonplace for treaties binding on the metropolitan state to be applicable in that state's colonies if the state made a declaration to this effect, via the operation of a 'colonial clause' in the treaty. This reflects concepts of trusteeship-over-people and civilizational difference which legitimized colonial rule in general and the role of the colonial authority in determining what standards were appropriate in colonial territories in particular. The colonial-clause model for applicability was adopted in the European Convention on Human Rights of 1950 and certain of its Protocols, but not other subsequent human rights treaties. The standard jurisprudential view is that in the absence of a colonial clause declaration, the Convention cannot be applicable on the alternative basis on which it operates in a state's territory and to its extraterritorial activities. Such a declaration of applicability was not made in relation to the Chagos Islands, a UK colony, where human rights questions have been raised by the forced displacement by the UK of the indigenous population between 1968 and 1973, the continued denial of this people of their right to return, and more recent allegations concerning the US military base on one of the islands, Diego Garcia. However, in a 2012 decision, the European Court of Human Rights suggested that the standard position on the exclusive determinacy of declarations under the colonial clause may no longer be sustainable. The present piece takes this suggestion and explores its potential, taking into account the significance of the self-determination entitlement in having delegitimized the underlying concepts of trusteeship and civilizational difference on which the standard position is based.